2013
DOI: 10.1212/01.wnl.0000436949.75473.79
|View full text |Cite
|
Sign up to set email alerts
|

Predicting stroke mortality

Abstract: Physicians, patients, and families rely on clinical factors associated with stroke mortality to guide decisions of care and set goals of medical therapy. However, these factors, including age and baseline neurologic impairment, are at best imperfect predictors and additional prognostic tools are needed. Biomarkers such as B-type natriuretic peptide (BNP) have potential. However, for a biomarker to be of clinical utility, it needs to add information beyond what clinical predictors can provide. BNP is produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…BNP plasma and NT-proBNP serum levels are elevated in stroke pathology ( Table 1 ) and associated with increased mortality [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Montaner J. et al [ 104 ] identified that BNP plasma levels were higher among patients who died (118.2 vs. 60.9 pg/mL; p < 0.001), and multivariate logistic regression analysis indicated that the plasma BNP level was an independent predictor of death after stroke (BNP > 65.3 pg/mL; odds ratio (OR) = 1.97; p = 0.034).…”
Section: B-type Natriuretic Peptide Expression In Stroke Pathologymentioning
confidence: 99%
“…BNP plasma and NT-proBNP serum levels are elevated in stroke pathology ( Table 1 ) and associated with increased mortality [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 ]. Montaner J. et al [ 104 ] identified that BNP plasma levels were higher among patients who died (118.2 vs. 60.9 pg/mL; p < 0.001), and multivariate logistic regression analysis indicated that the plasma BNP level was an independent predictor of death after stroke (BNP > 65.3 pg/mL; odds ratio (OR) = 1.97; p = 0.034).…”
Section: B-type Natriuretic Peptide Expression In Stroke Pathologymentioning
confidence: 99%
“…BNP, a well-known biomarker for heart failure (HF), has now been identified as potentially useful for stroke patient prognostic and recovery management. BNP elevated serum levels in stroke patients show correlation with CEI stroke [90,[123][124][125][126][127][128][129][130][131][132][133][134][135], increased mortality [136][137][138][139][140][141][142][143] and indication of second stroke recurrence [144][145][146]. Cobas h 232 technology is based upon an immunological method and uses 150μL heparinized venous whole blood as sample material.…”
Section: Cobas® H 232 (Roche)mentioning
confidence: 99%
“…However, BNP measurement can also be valuable for stroke patient’s recovery. BNP elevated serum levels in stroke patients also show a correlation with increased mortality [115,116,117,118,119,121,122,124] and indication of second stroke recurrence [110,111,156]. By monitoring BNP levels in stroke patients in their recovery process, the clinical staff will be able to better understand the stroke patient's status by predicting mortality and preventing second stroke recurrence.…”
Section: Pocts Expedite Stroke Prognosticsmentioning
confidence: 99%
“…Glial cells’ origin stroke biomarkers include Protein S100-Beta (S100B) [157,158,161,162,163,164,165], Glial Fibrillary Acidic Protein (GFAP) [157,161,162,166,167,168,169,170,171] and Myelin Basic Protein (MBP) [172,173,174,175], whereas that for Neuronal cells include, Neuron-Specific Enolase (NSE) [129,157,158,161,162,163,166,176,177], Ubiquitin Carboxyl-terminal Hydrolase L1 (UCH-L1) [157,158,178,179,180,181] and Creatine Kinase-BB (CK-BB) [182,183]. On the other hand, Heart muscle cells (cardiomyocytes) include B-Type Natriuretic Peptide (BNP) [87,100,101,102,103,104,105,106,107,108,110,111,112,113,114,115,116,117,118,119,120,121,…”
Section: Key Elements In Novel Stroke-poctsmentioning
confidence: 99%